Methods of the Pattern Recognition in the Uzbek Language on the Basis of Cellular Automata - Turkmenova Rukhiye Tokhirovna (Periodica Journal, 2022)
The article describes the usage of the method of cellular automata in the OCR in the Uzbek language on the basis of the intersecting allocation algorithms, ends and symbol loops, allocation of endpoints and intersections
Keywords: automata; recognition; image; algorithms